Intraocular Pressure Assessment in Pediatric Cases Receiving Long-Term Seasonal Allergic Conjunctivitis Treatment - Cafer Tanrıverdi; Goktug Demirci; Sevil Karaman Erdur; Ozlem Balci; Mustafa Özsutcu; Cengiz Aras; Burcu Nurözler Tabakcı (Van Tıp Dergisi, 2021)
INTRODUCTION: To investigate the effect of seasonal drugs on intraocular pressure (IOP) in the long term in pediatric age group who are followed up and treated with seasonal allergic conjunctivitis (SAC) diagnosis. METHODS: The study included 230 cases under the age of 16 who received SAC treatment for 5 years or more (Group I), and 255 healthy cases under the age of 16 in the control group (Group II). IOP measurements of the patients were made with non-contact tonometry. Mean IOP values of both groups were statistically compared. RESULTS: The mean age of the patients included in the study was 9.3+-2.0 in group I and 9.1+-2.1 in group II. The mean duration of treatment in SAC patients was 5.3+-0.7 years. In group I, the mean IOP was 13.7+-3.1 mmHg in the right eye, 13.7+-2.8 mmHg in the left eye, while in group II the mean IOP was 13.8+-3.1 mmHg in the right eye and 13.9+-3.0 mmHg in the left eye. There was no statistically significant difference between the mean IOP values of two groups (P>0.05). Temporary IOP elevation due to corticosteroid treatment was observed in 11 patients (4.8%) in group I. In all these patients, IOP lowered to normal limits after corticosteroid treatment discontinued. DISCUSSION AND CONCLUSION: It was observed that medical treatment, which is given periodically with the diagnosis of SAC in pediatric cases, does not have a permanent effect on IOP in the long term. We think that close follow-up is important to realize possible acute IOP elevation in these patients.